CSR and Entrepreneurship: Drivers for Social Responsibility in German Business Start-Ups - Weiss, Stephanie (2013)
The relationship between entrepreneurship and ethics is complex and multifaceted (Fisscher, et al., 2005). When a firm comes into existence, it enters relationships with various stakeholders (Mitchell & Cohen, 2006). Other than merely managing different stakeholder claims, entrepreneurs are forming relationships with stakeholders from private and professional networks, who provide the knowledge and resources needed to found and establish a business (Dimov, 2007). As a result, attention to stakeholder interestes is a critical factor for the success of newly found businesses (Choi & Shepherd, 2005). The complex relationship between entrepreneurship and stakeholder theory provides the frame of this study which examines social responsibility drivers in German business start-ups. Drawing on literature from the fields of Corporate Social Responsibility (CSR) in small and medium sized businesses, entrepreneurship and stakeholder theory, two research questions have been developed addressing research gaps regarding the micro-foundations of responsibility in entrepreneurship. The aim of this study is to identify driving factors which influence entrepreneurs of newly founded firms to act responsibly. Taking a case study approach, six start-up companies from the e-commerce sector have been compared to gain an insight into the similarities and differences in driving factors for responsibility across different firms. The findings suggest that a complex set of personal, stakeholder and economic drivers influence entrepreneurs to act socially responsible, whereby influences most commonly referred to in the literature (personal values, resource dependency, economic challenges and trade-offs) could not fully explain why some entrepreneurs behave responsibly while others do not. Rather, the research suggests that a different approach to building legitimacy and reliability of a newly established firm plays a role in influencing entrepreneurs’ propensity to act socially responsible.